Application of The Game Based Learning Model to Increase Student Learning Participation in PJOK Learning - Fauziah, Nadila Nurul; Fahrudin; Gustiawati, Resty; Ernawati, Neneng (STKIP Pasundan, 2025)
This study aims to analyze the effectiveness of the application of the Game Based Learning (GBL) model in increasing student involvement during Physical Education, Sports, and Health (PJOK) learning. The type of research used is Classroom Action Research (PTK) which is carried out in one cycle, including the stages of planning, implementation, observation, and reflection. The research subjects were taken from SMK Bhineka Karawang which consisted of 32 students in class X TSM 1 for the 2024/2025 school year. Data was collected through questionnaires and observations to measure student participation in the learning process. The results of the study showed a significant increase in student interest and participation with an average questionnaire score of 4.56 from the Likert scale or equivalent to 90.7% (very good category). These results show that the application of Game Based Learning is able to create more active, interesting, and collaborative PJOK learning.